Currency hierarchy and financial globalization in emerging economies: how far does Riese's critique of growth by external debt still hold? - Barbara Fritz; Luiz Fernando de Paula; Daniela Prates (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2022)
How has financial globalization changed the nature of the external vulnerability of emerging economies? The authors first present an overview of the changes in international capital flows and cross-border stocks involving emerging economies from the 1970s to the COVID-19 crisis, and then identify relevant recent shifts in financial globalization. They depart from the critique of growth by debt strategies, put forward, among others, by Riese, and the concept of currency hierarchy. Their question is whether this critique still holds when one considers the main recent features of financial globalization. They find that Riese's contributions are still relevant when analysing the external vulnerability of emerging-market economies (EMEs), even with caveats that stem from his oversimplified view of the financial sector. They conclude that financial vulnerability overall has not decreased, but rather has changed its nature and the channels through which it affects EMEs, becoming more complex.
Keywords: 330; external vulnerability; currency hierarchy; subordinated financial integration; financial globalization; emerging-market economiesF32; F34; F62